Comic Language Means in the English-Language Comic Books - K. A. Radyuk (Дискурс профессиональной коммуникации, 2022)
The article is devoted to the study of language means used to create a pragmatic effect of humour and the comic in English-language comic books. The issue is considered in the context of studying the comic book not only as a creolised text and a special literary tradition, but also as a separate type of artistic discourse with a set of characteristic functional-linguistic parameters. Understanding the cognitive-discursive mechanism of humour in a graphic work is of particular interest in terms of optimising the creative and professional interaction between the artist and the author of the narrative text, who often act as a collective producer of modern comic book discourse. The empirical material of the study comprises examples of comic situations from various issues of comic books by Marvel and DC pub- lishing houses related to different topics, formats and time periods. Observation, quantitative analysis, the use of discursive means of the comic, linguistic-pragmatic analysis of humorous situations and generalisation of the obtained statistical groups and their interaction are used as methods of the research. In the article, the author proposes the definition of a comic book as a type of text and a separate type of artistic discourse, as well as distinguishes it from purely humorous types of graphic literature. The study differentiates between the terms “device” and “means” in the context of humorous pragmatics, offers a classification of comic means, as well as gives a brief description of them. In this article, an attempt is made to identify stylistic and functional-pragmatic features of the use of a number of means of creating a comic effect in the semantic structure of an English comic book. As a result of the study, the author formulates conclusions about the influence of the graphic component on the manifestation of the means of the comic, intertextual orientation and the interconnectedness of these means, as well as the functional load of humour in the English comic book.